Play to aspire and create new realities - Barbosa Lopes, José Carlos; Vendramini-Zanella, Daniela; Fuga, Valdite Pereira (DELTA: Documentação e Estudos em Linguística Teórica e Aplicada, 2023)
This paper discusses core principles such as play, collaboration, and agency that support the online workshops offered by the Global Play Brigade (GPB), an international community of activists from different areas, who got together to fight against the global crisis that threatened the world in so many ways due to the covid-19 pandemic. To exemplify part of the theoretical and methodological approach involved in the plan and, the workshop, as well as its goals, one of the sessions will be described along with perspectives aligned to Spinoza, Vygotsky, Freire, and some other authors to promote understanding of how people can be affected towards social change. It is known that there are many facets to the current turmoil, so the GPB seeks to create spaces in which creativity and critical thinking can create possibilities for emotional support, development, hope, and action.